Divergent proinflammatory immune responses associated with the differential susceptibility of cattle breeds to tuberculosis - Kumar, Rishi; Gandham, Sripratyusha; Rana, Avi; Maity, Hemanta Kumar; Sarkar, Uttam; Dey, Bappaditya (Frontiers in Immunology, 2023)
Tuberculosis (TB) in the bovine is one of the most predominant chronic debilitating infectious diseases primarily caused by Mycobacterium bovis. Besides, the incidence of TB in humans due to M. bovis, and that in bovines (bovine TB, bTB) due to M. tuberculosis- indicates cattle as a major reservoir of zoonotic TB. While India accounts for the highest global burden of both TB and multidrug-resistant TB in humans, systematic evaluation of bTB prevalence in India is largely lacking. Recent reports emphasized markedly greater bTB prevalence in exotic and crossbred cattle compared to indigenous cattle breeds that represent more than one-third of the total cattle population in India, which is the largest globally. This study aimed at elucidating the immune responses underlying the differential bTB incidence in prominent indigenous (Sahiwal), and crossbred (Sahiwal x Holstein Friesian) cattle reared in India. Employing the standard Single Intradermal Tuberculin Test (SITT), and mycobacterial gene-targeting single as well as multiplex-PCR-based screening revealed higher incidences of bovine tuberculin reactors as well as Mycobacterium tuberculosis Complex specific PCR positivity amongst the crossbred cattle. Further, ex vivo mycobacterial infection in cultures of bovine peripheral blood mononuclear cells (PBMC) from SITT, and myco-PCR negative healthy cattle exhibited significantly higher intracellular growth of M. bovis BCG, and M. tuberculosis H37Ra in the crossbred cattle PBMCs compared to native cattle. In addition, native cattle PBMCs induced higher pro-inflammatory cytokines and signaling pathways, such as interferon-gamma (IFN-γ), interleukin-17 (IL-17), tank binding kinase-1 (TBK-1), and nitric oxide (NO) upon exposure to live mycobacterial infection in comparison to PBMCs from crossbred cattle that exhibited higher expression of IL-1β transcripts. Together, these findings highlight that differences in the innate immune responses of these cattle breeds might be contributing to the differential susceptibility to bTB infection, and the resultant disparity in bTB incidence amongst indigenous, and crossbred cattle.